AN OVERVIEW OF THE MEANS TO ENHANCE TOMATO SEED PHYSIOLOGICAL QUALITY IN THE CONTEXT OF SUSTAINABLE HORTICULTURE - Elena DELIAN; Beatrice IACOMI; Lenuța CHIRA; Silvana GUIDEA-DĂNĂILĂ; Adrian CHIRA; Andreea COȘOVEANU (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
The tomato (Solanum lycopersicum L.) is one of the most cultivated vegetable species worldwide, both in protected areas, as well as in open - field conditions, due to the preferences of consumers for this vegetable, its nutritive and nutraceutical value, also its multiple processing possibilities. At the same time, tomatoes are model plants for studies on fruit growth, development and ripening. Along with many other common factors that influence the quality of tomatoes (variety, cultural practices, timing and method of harvesting, handling, transport and storage) and taking into account the various growing conditions and possible exposure to the action of various stress factors, the primary condition for good growth and development of plants (including for promoting yield, fruit quality value, as well as technological properties) is the use of a seed characterized by a high physiological quality. In this context, the different seed priming techniques have proved effective both in favor of the germination process and increasing the vigor of the seedlings, as well as in terms of enhancing the crop productivity within the different cultivation systems. Besides these, the quality of the fruits at the time of harvest, as well as their behavior in the post-harvest period proved to be beneficially influenced by the treatments applied to the seeds. This short overview presents some noteworthy research results obtained in the last decade for tomatoes, which have proven to be of interest from the economical, environmental protection and human health viewpoint in the context of increasing sustainability.